Parents' Strategies To Get Children Used To Giving Charity - Putri Salsabila; Isnaini Kurnia Syahri; Wirda Hayani Syahputri; Masganti Sit (Sean Institute, 2024)
The role of parents is very important in shaping the character and religious development of children , through charity activities . Charity is part of worship in Islam that teach the values of goodness , social concern , and sincerity . This articles aiming to identify and evaluate strategies that can be carried out by parents in developing religious aspects in children through the habits of charity . Some strategies that can be applied include providing direct examples , teaching the meaning and benefits of charity , involving children in charity activities , giving special tasks to set aside part of the wealth , and holding a regular charity schedule . Through this approach , it is hope that children can grow into religious , caring individuals who have high social awareness . This articles also highlights the challenges face by parents in teaching children the values of charity based worship .